2015
DOI: 10.1016/j.optlastec.2015.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Spectral modification of mode structures in silver nanoparticle doped Rhodamine 6G

Abstract: a b s t r a c tWe show in our work that very narrow (FSR $ 0.09 nm) lasing modes can be formed from Rhodamine 6G solution confined within quartz (SiO 2 ) cuvette with suitable pumping scheme by Q switched Nd:YAG laser. With introduction of silver nanoparticles of different concentrations in Rhodamine 6G we show that such lasing modes can be modulated as well as tuned in intensity, band spacing and emission wavelength. We also show that this system maintains a very high Q value 46.4*10 3 irrespective to change … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The produced composite particles (i.e., Cu 2 O/NCC‐EDA) indicate that the diffraction peaks representing Cu 2 O highly resemble those of pure Cu 2 O, except that the peak edges shift toward larger angles, and the full width at half maximum (FWHM) of the XRD peaks increases slightly. According to the equation 2 d sin θ = nλ , θ increases with the decrease of lattice spacing d ; thus, the possible reason for the shift of Cu 2 O peaks is that the NCC‐EDA coating prevents further growth of Cu 2 O crystals, thereby leading to reduced lattice spacing and smaller particle size. The increase of the FWHM also indicates that the size of Cu 2 O in the composite particles decreases .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The produced composite particles (i.e., Cu 2 O/NCC‐EDA) indicate that the diffraction peaks representing Cu 2 O highly resemble those of pure Cu 2 O, except that the peak edges shift toward larger angles, and the full width at half maximum (FWHM) of the XRD peaks increases slightly. According to the equation 2 d sin θ = nλ , θ increases with the decrease of lattice spacing d ; thus, the possible reason for the shift of Cu 2 O peaks is that the NCC‐EDA coating prevents further growth of Cu 2 O crystals, thereby leading to reduced lattice spacing and smaller particle size. The increase of the FWHM also indicates that the size of Cu 2 O in the composite particles decreases .…”
Section: Resultsmentioning
confidence: 99%
“…Following the recombination of Cu 2 Oa nd NCC-EDA, the diffraction peak representing NCC-EDAi nt he product shifts to higher 2q values.W ithin the range of 158-508,r elatively wide peaks are observed that correspond to the graphite (002) crystalp lane.T his is likely caused by the introduction of Cu 2 Oa ccelerating the graphitization of NCC-EDA.T he produced compositep articles (i.e., Cu 2 O/ NCC-EDA)i ndicate that the diffraction peaks representing Cu 2 Oh ighly resemble those of pure Cu 2 O, except that the peak edges shift towardl arger angles,a nd the full width at half maximum(FWHM) of the XRD peaks increases slightly. Accordingt ot he equation 2 dsinq = nl, [25] q increases with the decrease of lattice spacing d;thus, the possible reason for the shift of Cu 2 Op eaks is that the NCC-EDAc oating prevents further growtho fC u 2 Oc rystals,t hereby leading to reduced lattice spacing and smaller particle size.T he increase of the FWHM also indicates that the size of Cu 2 Oi nt he composite particles decreases. [26] This observation agrees with the TEM results,w hich further show that the encapsula-tion of NCC-EDA suppresses the growth of Cu 2 Oi nt he composite particles.…”
Section: Structure Of Cu 2 O/ncc-edamentioning
confidence: 99%